Analisis Penggunaan Alat Pelindung Diri pada Pekerja di PT.Djabesmen Menggunakan Metode Fishbone - Susanto, Agus Dwi; Momon, Ade (Fakultas Teknik Universitas Tulang Bawang, 2024)
The possibility of accidents in a building project is one of the causes of hampering the effectiveness of project work activities. Workers are required to implement a good occupational safety and health (K3) management system to minimize the possibility of work accidents. An example of a case in the construction world occurred in the Gading Mediterania Apartment construction project located in Kelapa Gading. The accident that occurred killed four workers. Two people were killed by precast concrete and two people died from electric shock. Therefore, to prevent the recurrence of the incident, research was conducted using fishbone analysis. The purpose of this research is to analyze the importance of using personal protective equipment at PT Djabesmen. The method used helps the author in analyzing the possibility of accidents on the project. The results of the analysis explain that the percentage of PPE use at PT Djabesmen is good. Keywords: Analysis, Fishbone, K3